2013
DOI: 10.5430/afr.v2n2p59
|View full text |Cite
|
Sign up to set email alerts
|

A Vector Error Correction Modeling of Security Spending and Economic Growth in Nigeria

Abstract: The study has been on the impact of security expenditure on the level of economic growth in Nigeria. Using data covering the period between 1980 and 2010, the ECM result shows that the expenditure on defence has a negative impact on the level of economic growth. An indication of flawed expenditure budgeting and implementation in the defence sector. Expenditure on internal security played important role in generating the desired level of economic growth in Nigeria. The low elasticity indicates that the signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The results revealed no direction of causality between banking sector development and Nigerian real estate growth. Oriavwote and Eshenake (2014) examined the impact of financial sector development on economic growth using GDP to measure economic growth and domestic credit to the private sector with multiple regression technique. The results indicated that financial development had no impact on economic growth based on the statistical insignificance of credit to the private sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results revealed no direction of causality between banking sector development and Nigerian real estate growth. Oriavwote and Eshenake (2014) examined the impact of financial sector development on economic growth using GDP to measure economic growth and domestic credit to the private sector with multiple regression technique. The results indicated that financial development had no impact on economic growth based on the statistical insignificance of credit to the private sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Empirical findings on the relationship between expenditure on internal security and economic growth have been uneven; Oriavwote and Eshenake (2013) employed an error correction model to examine the impact of security expenditure on economic growth in Nigeria spanning 1980 and 2010. The result revealed that government expenditure on internal security has a positive and significant relationship with economic growth.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…However, this study disaggregated spending on internal security into capital and recurrent spending. Then replaced expenditure on defence with other relevant independent variables (i.e., interest rate and exchange rate) not captured in the study of Oriavwote and Eshenake (2013) to actually showcase the influence of internal security expenditure among other vibrant variables on the economic growth of Nigeria. Strictly speaking, the current model states that Nigeria's economic growth depends on recurrent expenditure on internal security, interest rate, and exchange rate.…”
Section: Framework Specificationmentioning
confidence: 99%
“…The authors of these studies used different econometric methodologies, such as ARDL, descriptive methods and OLS, among others. The results of these studies were mixed, with some indicating a strong correlation between financial inclusion and economic growth (Nwanne, 2015;Oriavwote and Eshenake, 2014;Ammar and Azhar, 2015;Bongomin et al, 2018;Fowowe and Folarin, 2019;Grohmann et al, 2018;Ozili, 2018;Swamy, 2014;Adegbite and Machethe, 2020;Cicchiello et al, 2021), whereas others found little or no correlation (Olofin and Uduma, 2006).…”
Section: Impact Of Financial Inclusion On Economic Growthmentioning
confidence: 99%